The EU Consolidated Income Tax Revisited - Sylvain Plasschaert (Center for Economic Studies and ifo Institute (CESifo), 2002)
This article reviews the main technical and policy problems which the implementation of two formats of comprehensive solutions, discussed in the recent report by the Commission on Company Taxation in the Internal market' would require. Both approaches imply the consolidation within the EU of net profits, but diverge as regards the competence to fix the rate. The paper also suggests some variants to these two basic models.
Keywords: 330